The factor that influences employees job satisfaction: an examination of employees at Permodalan Nasional Berhad, Kuala Lumpur / Kamaruleliayana Kamarudin - Kamarudin, Kamaruleliayana (Faculty of Business and Management, 2009)
This study examines what are the most factors that influence job satisfaction among employees at Pemodalan Nasional Berhad, Kuala Lumpur. As a big investment company in Malaysia, they must play vital role in managing the organization as well as managing the people itself which is align with the organization objective. Only when employees satisfy can make the organization be more committed and success. The problem identified in this situation is that absenteeism and turnover. The several objectives in this study are to identify the most factors that influence the job satisfaction. Second objective is to identify the level of job satisfaction among employees and lastly to identify the relationship between the independent and dependent variable. Research design of this study is descriptive study research. The questionnaires will be the closed-ended questions. The target population in this study is consisting of 50 employees. For this study, the sampling technique uses simple random sampling. Data analysis and interpretation use SPSS software. Reliability Statistics result is reliability of the measures used in this study can be considered to be good. The summary of demographic statistic shows that most of the respondents are males and executives. They are also between the age of 36-45 years old and already married. Most of them hold a degree with a level income range from RM3000 – RM4000. Summary Statistics for independent and dependant variables shows that most of the respondents’ answers for the dependent variable, employee satisfaction is satisfied. For the independent variables, most of the respondents circle the ‘neither dissatisfied nor satisfied for the management sections. For independent variables which are pay, co-worker and environment, the respondents are satisfied according to the mean which is 3.68, 4.04 and 3.78 respectively. The factors that most influence job satisfaction among employees at PNB are co-worker, followed by working environment and pay. Last factor is management. The level of satisfaction among employees at PNB is satisfied.